UPAYA GURU KELAS DALAM PEMBINAAN AKHLAK MULIA KELAS IV DI SD NEGERI 06 ARUNG PARAK TAHUN 2023-2024 - Erni Srihastuti; Susilawati; Patriana (CV. ADIBA AISHA AMIRA, 2026)
This study aims to uncover: 1) The implementation of the role of class teachers in fostering noble morals among fourth-grade students at SD Negeri 06 Arung Parak in the 2023-2024 academic year. 2) The inhibiting factors in fostering noble morals among fourth-grade students at SD Negeri 06 Arung Parak in the 2023-2024 academic year. This study employed a qualitative approach and phenomenological research. Data collection techniques included interviews, observation, and documentation. Data analysis techniques included data reduction, data display, and conclusions. Data validity was verified using source triangulation and member checking. The results of the study indicate that: 1. Class Teacher Implementation in Fostering Noble Morals in Grade IV Students at SD Negeri 06 Arung Parak in the 2023-2024 Academic Year includes: 1) supervising children's social interactions at school; 2) accustoming children to religious practices; 3) instilling compassion for others; 4) Role Modeling; 5) Advice; 6) Prohibition; 7) Punishment; 8) Habituation.